Dear Friend: letters & essays of Elias Hicks - Hicks, Elias (Inner Light Books, 2011)
In the course of his life, Elias Hicks (1748-1830) penned hundreds of letters, while writing only one book. The Journal of Elias Hicks is a record of service to the Religious Society of Friends, revealing a man repeatedly called by God to travel among and minister to Quakers in North America. In the Journal, he describes the hundreds of Quaker meetings he visited, scores of public meetings he conducted, and gives some account of his life as a Long Island farmer. Complementing the framework in the Journal, Hicks' letters flesh out the details of his life and his beliefs. They reveal a thoughtful man of deep devotion -- a man devoted to his wife and family, to his neighbors and friends, to the Religious Society of Friends, but more than anything else, a man simply, humbly, and steadfastly devoted to God. Some of his letters recount the trials of a traveling minister in the early 19th century. Others lay out his understanding of what it means to live faithfully as a Quaker in those times of conflict and change. Most controversially, some put forward his theological beliefs and the scriptural basis for them. Paul Buckley has compiled and transcribed a selection of Elias Hicks' letters and essays from the original manuscripts. To aid the reader, he has added footnotes and scriptural citations to the text, as well as appendices explaining Quaker terms and structures, definitions of archaic and unfamiliar words and phrases, and biographical sketches. -- Publisher's description